A case of hepatosplenic sarcoidosis accompanied by hypercalcemia: Hepatosplenic Sarcoidosis - Fakılı, Füsun; Bayram, Nazan Gülhan; Uzun, Evren (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
We present a case diagnosed with hepatosplenic sarcoidosis with hypercalcemia. Elevated liver enzymes and hypercalcemia were detected in the patient who was admitted to the hospital with abdominal pain and dyspnea. Abdominal dynamic magnetic resonance imaging (MRI) showed diffuse, multiple, nodular hyperintense lesions on T2 weighted. Multinuclear giant cells and lymphocytic portal inflammation were seen in the patient's liver biopsy, whose angiotensin-converting enzyme level was high, and hepatosplenic sarcoidosis was diagnosed. Shortness of breath, abdominal pain, and calcium level improved with methylprednisolone treatment.